RISE Up: Facilitating Frontline Responder Collaboration on Co-Occurring Child Welfare and Intimate Partner Violence Cases - Langenderfer-Magruder, Lisa (Journal of interpersonal violence, 2021)
Intimate partner violence (IPV) services are necessary in numerous human service systems, requiring responders (e.g., victim services, law enforcement, social service providers) to collaborate with one another to best meet the needs of their respective clients. Child welfare workers, in particular, carry caseloads with a high prevalence of IPV, yet have reported significant barriers to successful collaboration with other responder roles, such as tension regarding who is the primary client (i.e., the IPV victim or the child). This study explores the qualitative responses of child welfare workers in Florida to understand their collaboration experiences, focusing specifically on their perceptions of facilitative factors of collaboration. Data were collected in Wave 4 of the Florida Study of Professionals for Safe Families, an ongoing longitudinal study of turnover among newly hired child welfare workers. Participants in child welfare and health and human services roles were asked to provide a response to the open-ended item: “What is most helpful in establishing strong collaborations with other responders on cases that involve intimate partner violence?” To better contextualize the results, the analytic sample was ultimately reduced to 526 child welfare workers currently employed in Florida who reported ever working on cases with IPV and provided a response to the open-ended item. Based on a thematic analysis, findings lend to a conceptual model of IPV collaboration among frontline workers that promotes institutional empathy through a cumulative building of communication, rapport, appreciation for teamwork, and consistent understanding of case processes: The Responder InStitutional Empathy (RISE) model of collaboration. Frontline worker efforts to improve collaboration would be bolstered by the accompanying efforts of leadership. The authors suggest increasing mechanisms to promote joint work between responder roles, such as cross-training and colocation.